2004
DOI: 10.1080/03655230410017715
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of the odor stick identification test for the Japanese in patients suffering from olfactory disturbance

Abstract: We studied the suitability of the Odor Stick Identification Test for the Japanese (OSIT-J) in patients suffering from olfactory disturbance. In 120 patients with olfactory disturbance (age range 12-85 years) there were statistically significant correlations between the odor identification rate on the OSIT-J, the results of the Japanese standardized olfactory test (T&T olfactometry) and subjective symptom scores. In every patient treated for olfactory disturbance, the OSIT-J reflected the grade of recovery from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 5 publications
(10 reference statements)
1
17
0
2
Order By: Relevance
“…Recently, the odor stick identification test for Japanese (OSIT-J) was developed by Saito, Ayabe-Kanamura (25,26) as a new type of smell identification test; it consists of 13 odorants that are all familiar to Japanese subjects. A significant correlation coefficient between the identification rate of OSIT-J score and the results of T&T olfactometry has been reported both in normal Japanese subjects and in patients with olfactory disturbances (27,28). The OSIT score has been shown to be significantly correlated with the CC-SIT score, but the average identification rate using the OSIT was significantly higher than that using the CC-SIT (26 …”
Section: Employed the 40-odorant University Of Pennsylvania Smell Idmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, the odor stick identification test for Japanese (OSIT-J) was developed by Saito, Ayabe-Kanamura (25,26) as a new type of smell identification test; it consists of 13 odorants that are all familiar to Japanese subjects. A significant correlation coefficient between the identification rate of OSIT-J score and the results of T&T olfactometry has been reported both in normal Japanese subjects and in patients with olfactory disturbances (27,28). The OSIT score has been shown to be significantly correlated with the CC-SIT score, but the average identification rate using the OSIT was significantly higher than that using the CC-SIT (26 …”
Section: Employed the 40-odorant University Of Pennsylvania Smell Idmentioning
confidence: 98%
“…The identification ratio of Japanese orange was 40% in normal subjects, and 31.5% in PD, respectively in our study. Previous studies showed that the identification ratio of Japanese orange was lowest in normal subjects (26,27), and was below 70% in normal subjects aged from 20 to 80 years, and was also lower in patients with olfactory dysfunction (28) because subjects chose "apple" in error (26,28). In the present study, the reason why the identification ratio of Japanese orange in normal subjects was lower than that in the previous studies was that the age of normal subjects was older (mean age 69.7 years).…”
Section: F I G U R E 1 Co Mp a R I S O N O F C O R R E C T O D O R mentioning
confidence: 99%
“…However, these tests are not appropriate for Japanese without modification because some smells are unfamiliar because of cultural differences. In this study, we used the Odor Stick Identification Test for Japanese (OSIT‐J),9–11 developed specifically for Japanese and with confirmed efficacy, in patients with iRBD and PD. We investigated the frequency of olfactory disorders in these conditions and the utility of the OSIT‐J as a supportive tool for their diagnosis.…”
mentioning
confidence: 99%
“…Simple odor presentation devices have been developed for the screening of olfactory impairment in Japan. The Odor Stick Identification Test for the Japanese (OSIT-J; Daiichi Yakuhin Sangyo, Tokyo, Japan) [2] has proven useful for identifying patients with olfactory impairment in otorhinolaryngological clinics [3,4]. The OSIT-J consists of 12 odorants that are familiar for Japanese people [2].…”
Section: Introductionmentioning
confidence: 99%